Hubungan Motivasi dengan Prestasi Belajar Bahasa Arab Ditinjau dari Kemampuan Awal Siswa SD Islam Ar-Raafi - Asriadi Asriadi; Mardhiana Jamal; Ambo Dalle (Lembaga Yasin AlSys, 2026)
Although internal factors such as motivation have increasingly received attention in language learning research, studies that specifically examine the role of prior ability (entry behavior) as a moderator in the relationship between learning motivation and learning achievement remain limited. This study aims to analyze the role of prior ability in moderating the relationship between learning motivation and Arabic language learning achievement. This study employed a quantitative correlational approach with a moderation design, involving 40 sixth-grade students of SD Islam Ar-Raafi selected through total sampling. The research process was conducted during the odd semester in November 2025. Data were collected using a Likert-scale questionnaire to measure learning motivation and score documentation for prior ability and learning achievement, and were then analyzed using Moderated Regression Analysis (MRA) with the assistance of SPSS. The results showed that learning motivation, with a mean of 85.98, and prior ability, with a mean of 87.77, were in the moderate category, whereas learning achievement, with a mean of 89.25, was classified as good. The MRA analysis proved that prior ability significantly strengthened the relationship between learning motivation and learning achievement, as indicated by a significance value of 0.007 < 0.05 and an interaction coefficient of 0.002. This study also found an anomaly in that students’ high ambition was sometimes accompanied by amotivation in the form of loss of focus in understanding the material. These findings contribute to the development of motivation theory in educational psychology while broadening understanding of language acquisition. The conclusion of this study confirms that high motivation will have an optimal impact on learning achievement when supported by strong prior ability, so teachers need to provide a review of basic material through a matriculation program. The implications of this study include theoretical contributions to the literature on prior ability in Arabic language learning and practical implications for educational institutions to facilitate enrichment programs, while also opening opportunities for further research using a qualitative approach related to factors of students’ learning confusion.